Implementasi ITIL® V3 Framework pada Perancangan Aplikasi Service Desk Management Berorientasi User3 - Budiyono; Eko Nugroho; Wing Wahyu Winarno (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2012)
Information Technology Infrastructure Library (ITIL) provides a range of processes models and best practice functions as a guide in the alignment of IT and business process. Service Desk is the main function in ITIL to manage and handle all Incidents and Request from users of IT services. One of the main problems encountered in the implementation of Service Desk is the fact that some users are requesting IT services without following the procedure, they ask for help directly to IT personel. This study attempts to minimize those problems by designing Service Desk application using User Centered Design method. Users are expected to be able to use this application with ease and without constraints, thus leading to an increase in the active role of users in the Service Desk. This research was conducted in the PT. Bakrie Telecom Tbk. Application design on this research was done using WSDM (Web Site Design Method). Application design was tested based on three aspects, Navigation Quality testing, Navigation testing using a Test-Case, and testing user response through a survey. The test results prove that the overall design of Service Desk applications built using User Centered Design method have a better usability, making it more attractive to users and is expected to increase the participation of users in the Service Desk.